Care Trajectories of Veterans in the 12 Months After Hospitalization for Acute Ischemic Stroke. (October 2015) - Arling, Greg; Ofner, Susan; Reeves, Mathew J.; Myers, Laura J.; Williams, Linda S.; Daggy, Joanne K.; Phipps, Michael S.; Chumbler, Neale; Bravata, Dawn M.
Abstract : Background—: Recovery after a stroke varies greatly between individuals and is reflected by wide variation in the use of institutional and home care services. This study sought to classify veterans according to their care trajectories in the 12 months after hospitalization for ischemic stroke. Methods and Results—: The sample consisted of 3811 veterans hospitalized for ischemic stroke in Veterans Health Administration facilities in 2007. Three outcomes—nursing home care, home care, and mortality—were modeled jointly >12 months using latent class growth analysis. Data on Veterans' care use and cost came from the Veterans Administration and Medicare. Covariates included stroke severity (National Institutes of Health Stroke Scale), functional status (functional independence measure score), age, marital status, chronic conditions, and prestroke ambulation. Five care trajectories were identified: 49% of Veterans had Rapid Recovery with little or no use of care; 15% had a Steady Recovery with initially high nursing home or home care that tapered off; 9% had Long-Term Home Care; 13% had Long-Term Nursing Home Care; and 14% had an Unstable trajectory with multiple transitions between long-term and acute care settings. Care use was greatest for individuals with more severe strokes, lower functioning at hospital discharge, and older age. Average annual costs were highest for individuals with the Long-Term Nursing Home trajectory ($63 082), closely followed by individuals with the Unstable trajectory ($58 720). Individual with the Rapid Recovery trajectory had the lowest costs ($9271). Conclusions—: Care trajectories after stroke were associated with stroke severity and functional dependency and they had a dramatic impact on subsequent costs. Abstract : Supplemental Digital Content is available in the text.